Adherence to prophylaxis and its association with activation of self‐management and treatment satisfaction. Issue 4 (21st May 2021) - Hoefnagels, Johanna Wilhelmina; Schrijvers, Liesbeth Hélène; Leebeek, Frank W. G.; Eikenboom, Jeroen; Schols, Saskia E. M.; Smit, Cees; Schutgens, Roger E. G.; Gouw, Samantha C.; Fischer, Kathelijn; ,
Abstract: Introduction: Prophylactic replacement therapy (prophylaxis) in patients with haemophilia (PWH) requires lifelong, frequent (self)infusions. Prophylaxis effectiveness depends on adherence, and the drivers of treatment adherence among PWH are unclear. Aim: To quantify prophylaxis adherence and associations between adherence and patients' treatment attitudes and satisfaction in a large cohort of children and adults with haemophilia. Methods: In a nationwide, cross‐sectional, questionnaire‐based study, PWH with complete information currently using prophylaxis were selected. Validated Hemophilia Regimen Treatment Adherence Scale‐Prophylaxis (VERITAS‐Pro; normalised score range: 0–100, optimum 0) measured treatment adherence; the Patient Activation Measure (PAM‐13; total score range 0–100, optimum 100) measured activation of self‐management; Hemophilia Patient Satisfaction Scale (Hemo‐Sat; range 0–100, optimum 0) measured treatment satisfaction. Groups were compared according to age (children: <12 years; adolescents: 12–18 years; adults >18 years) and adherence levels using non‐parametric tests, and correlations were assessed using Spearman's rho. Results: Among 321 participants (median age 33 years, interquartile range [IQR]:15–54 years), adherence was high (median VERITAS‐Pro total score 17, 89% adherent) but worsened with age, with median scores of 5, 14 and 20 in children, adolescents, adults, respectively ( p < .001). Attitudes towards treatment (median 66 vs. 68) participants and treatment satisfaction (12 vs. 10) were similar between adherent and non‐adherent patients. The VERITAS‐Pro total score was moderately correlated with PAM‐13 ( r = .41) but not with Hemo‐Sat ( r = −.11). Discussion: Prophylaxis adherence was high (89%) but decreased significantly with age and was not correlated with treatment attitude or treatment satisfaction.